Analisis Kegagalan Strategi Kampanye Ridwan Kamil - Suswono dalam Pilkada 2024 - Afnissa, Dyah Deviana; Amarilis, Putri Kusuma; Renova, Valiesca Daffah; Putranto, Algooth (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The 2024 Jakarta Governor and Deputy Governor Election served as a critical stage for the Ridwan Kamil and Suswono duo, supported by major political parties through the Koalisi Indonesia Maju (KIM) Plus coalition. Despite broad political backing and leveraging communication strategies across social media, traditional media, and grassroots engagement, the pair failed to secure victory. This study examines their political communication strategies, including media utilization, public response, and challenges faced, such as negative perceptions due to past scandals, black campaigns, and local resistance to their identity. Using a qualitative descriptive approach based on desk reviews, the study finds that while Ridwan Kamil-Suswono managed to capture public attention with flagship programs like Kartu Jakarta Maju and Riverway, obstacles such as smear campaigns and misalignment with Jakarta's local culture were key factors in their defeat. The findings highlight the importance of synergy between political communication strategies, understanding local community characteristics, and effective image management in winning political contests.